A glucocorticoid- and diet-responsive pathway toggles adipocyte precursor cell activity in vivo - Wong, Janica C. (Sci Signal, 2016)
Obesity is driven by excess caloric intake, which leads to the expansion of adipose tissue by hypertrophy and hyperplasia. Adipose tissue hyperplasia results from the differentiation of adipocyte precursor cells (APCs) that reside in adipose depots. Investigation into this process has elucidated a network of mostly transcription factors that drive APCs through the differentiation process. Using in vitro and in vivo approaches, our study revealed a signaling pathway that inhibited the initiation of the adipocyte differentiation program. Mouse adipocytes secreted the extracellular protease ADAMTS1, which triggered the production of the cytokine pleiotrophin (PTN) through the Wnt/β-catenin pathway, and promoted proliferation rather than differentiation of APCs. Glucocorticoid exposure in vitro or in vivo reduced ADAMTS1 abundance in adipocytes. In addition, mice fed a high-fat diet showed decreased Adamts1 expression in the visceral perigonadal adipose depot, which expanded by adipogenesis in response to the diet, and increased Adamts1 expression in the subcutaneous inguinal adipose depot, which did not induce adipogenesis. Similar to what occurred in mouse subcutaneous adipose tissue, diet-induced weight gain increased the expression of ADAMTS1, PTN, and certain Wnt target genes in the subcutaneous adipose depot of human volunteers, suggesting the relevance of this pathway to physiological adipose tissue homeostasis and the pathogenesis of obesity. Thus, this pathway functions as a toggle on APCs, regulating a decision between differentiation and proliferation and coordinating the response of adipose tissue to systemic cues.